2020
DOI: 10.1111/jiec.12998
|View full text |Cite
|
Sign up to set email alerts
|

A text mining analysis of the climate change literature in industrial ecology

Abstract: The literature on climate change research has evolved tremendously since the 1990s. The goal of this study is to use text mining to review the climate change literature and study the evolution of the main trends over time. Specific keywords from articles published in the special issue “ Industrial Ecology for Climate Change Adaptation and Resilience” in the Journal of Industrial Ecology are first selected. Details of over 35,000 publications containing these keywords are downloaded from the Web of Science from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The nonparametric techniques belong to the general family of ML whose main advantage is the use of algorithms to train often structurally complex models. ML approaches often achieve high accuracy thanks to their ability to capture and model nonlinear behaviors, which have made them very popular in the scientific community; ML has been used to model countless systems. Nevertheless, because ML models tend to be structurally complex, it is often more difficult to validate trained ML models. A commonly used synonym for ML is “data driven”, as in the models developed only from observed data as opposed to those from theoretically established physical reasoning.…”
Section: Methodsmentioning
confidence: 99%
“…The nonparametric techniques belong to the general family of ML whose main advantage is the use of algorithms to train often structurally complex models. ML approaches often achieve high accuracy thanks to their ability to capture and model nonlinear behaviors, which have made them very popular in the scientific community; ML has been used to model countless systems. Nevertheless, because ML models tend to be structurally complex, it is often more difficult to validate trained ML models. A commonly used synonym for ML is “data driven”, as in the models developed only from observed data as opposed to those from theoretically established physical reasoning.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Anderson et al (2021) [18] analyzed over 130,000 articles to explore the increasing diversity of ecological hypotheses and theories published over the past 80 years. Similar studies of publishing trends have explored ecological topics in high impact journals [19], showed the emergence of conservation biology as a separate discipline from ecology [20], analyzed the growth of interdisciplinarity in biodiversity science [21], tracked shifting popularity of topics within industrial ecology [22] and fish ecology [23], identified research themes in disease ecology [24], and pinpointed critical research gaps in conservation science [25] and pollination ecology [26]. Outside of academic articles, text mining can reveal important trends for environmental management and biodiversity conservation [27].…”
Section: Detecting Trends and Topicsmentioning
confidence: 98%
“…[22] analysed over 130 000 articles to explore the increasing diversity of ecological hypotheses and theories published over the past 80 years. Similar studies of publishing trends have explored ecological topics in high impact journals [23], showed the emergence of conservation biology as a separate discipline from ecology [24], analysed the growth of interdisciplinarity in biodiversity science [25], tracked shifting popularity of topics within industrial ecology [26] and fish ecology [27], identified research themes in disease ecology [28], and pinpointed critical research gaps in conservation science [29] and pollination ecology [30]. Outside of academic articles, text mining can reveal important trends for environmental management and biodiversity conservation [31].…”
Section: Recent Applications In Ecology and Evolutionmentioning
confidence: 99%